Improving Transungual Permeation Study Design by Increased Bovine Hoof Membrane Thickness and Subsequent Infection - Sebastian Kappes; Thilo Faber; Lotta Nelleßen; Tanju Yesilkaya; Udo Bock; Alf Lamprecht (MDPI AG, 2021)
Ungual formulations are regularly tested using human nails or animal surrogates in Franz diffusion cell experiments. Membranes sometimes less than 100 µm thick are used, disregarding the higher physiological thickness of human nails and possible fungal infection. In this study, bovine hoof membranes, healthy or infected with Trichophyton rubrum, underwent different imaging techniques highlighting that continuous pores traversed the entire membrane and infection resulted in fungal growth, both superficial, as well as in the membrane's matrix. These membrane characteristics resulted in substantial differences in the permeation of the antifungal model substance bifonazole, depending on the dosage forms. Increasing the thickness of healthy membranes from 100 µm to 400 µm disproportionally reduced the permeated amount of bifonazole from the liquid and semisolid forms and allowed for a more pronounced assessment of the effects by excipients, such as urea as the permeation enhancer. Similarly, an infection of 400-µm membranes drastically increased the permeated amount. Therefore, the thickness and infection statuses of the membranes in the permeation experiments were essential for a differential readout, and standardized formulation-dependent experimental setups would be highly beneficial.